Assessment of Investment Plan and Financing Strategy for Hobbyist-Based Marketplace as a New Business from PT XYZ - Putri Nadiya Intan Safira; Mandra Lazuardi Kitri (Jurnal Ilmu Sosial Politik dan Humaniora (Jisora), 2021)
PT XYZ is a successful technology enterprise, intends to open a new business line in e-commerce with unique selling propositions as a hobbyist-based marketplace. The marketplace, ABC, has built website and application generating event registration, communities, and articles. ABC still needs to reduce bugs and acquiring sellers to sell their products on. ABC needs to seek investments to fulfill the required financing at IDR 245,000,000 since PT XYZ needs to reallocate the money to another business. It firstly needs to determine the financial feasibility study of ABC with the capital budgeting method of NPV, IRR, and Payback Period. The amount of NPV at IDR 500,722,291.51, IRR at 13.32%, and PP at 4 years 2 months and 19 days are acceptable. The risk assessment with sensitivity analysis and Monte Carlo simulation determine the accounts that are risked by the assumption from the owners, the high risk are on Bike Selling quantity and COGS also Salary (Full-Time) with the probability of positive IRR at 97.80%. ABC wants to have financing schemes of 65%, 45%, and 25% equity where PT XYZ will give IDR 25,000,000 and intangible asset of IDR 61.600.000, this makes the 25% equity cannot be used, therefore it will be changed to 35.35% equity. With total share outstanding of 10.000 shares, the sales price of A, B, and C are IDR 46,199.55, IDR 43,803.40, and IDR 42,771.43 respectively. Capital structure analysis is needed to get the best value of ownership, yet, all alternatives can be used for attracting investors.